2013
DOI: 10.2147/copd.s51245
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation-related impairment of quality of life and work productivity in severe and very severe chronic obstructive pulmonary disease

Abstract: PurposeExacerbation-associated health-related quality of life (HRQoL) in patients with severe and very severe chronic obstructive pulmonary disease (COPD) is ill-defined. This study describes patterns, HRQoL, and the work productivity impact of COPD-related moderate and SEV exacerbations in patients with SEV/VSEV COPD, focusing on the chronic bronchitis subtype.Patients and methodsA US sample of SEV and VSEV COPD patients with recent moderate or SEV exacerbation was recruited. Along with the demographic and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 24 publications
1
40
0
2
Order By: Relevance
“…On the other hand, Villar Balboa et al 23 found that exacerbations and dyspnea were the best individual factors related to HRQOL. Solem et al 24 showed that the severity and frequency of disease-related exacerbations in subjects with COPD were associated with poor HRQOL and work productivity and activity impairment. The symptoms in pa- tients with more exacerbations may be more intense, and their HRQOL may be poorer.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Villar Balboa et al 23 found that exacerbations and dyspnea were the best individual factors related to HRQOL. Solem et al 24 showed that the severity and frequency of disease-related exacerbations in subjects with COPD were associated with poor HRQOL and work productivity and activity impairment. The symptoms in pa- tients with more exacerbations may be more intense, and their HRQOL may be poorer.…”
Section: Discussionmentioning
confidence: 99%
“…19 Many tools are available to monitor HRQoL in COPD, and have been reviewed elsewhere; 20 they may be generic (i.e. used in any health problem), respiratory-specific or COPD-specific (e.g.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Several studies measured HRQOL, by means of EQ-5D, in patients with COPD during stable phases of the disease [3][4][5][6] and during exacerbations. [7][8][9] In stable disease, the EQ-5D's ability to discriminate between GOLD stages has been shown for total score 3,4 and EQ-VAS, 5 but ceiling effects have also been reported for EQ-VAS. 4,10 Up to now, only one study has examined the responsiveness of EQ-5D after PR in patients with COPD, 10 showing a significant improvement in EQ-5D utility score and a trend toward significant increase in EQ-VAS.…”
Section: Introductionmentioning
confidence: 99%